"I feel I can live every minute if I choose to": participants' experience of a positive mindfulness programme. Issue 4 (2nd October 2017) - Perridge, David; Hefferon, Kate; Lomas, Tim; Ivtzan, Itai
ABSTRACT: Both separately and together, mindfulness and positive psychological interventions have been found to increase wellbeing against a number of measures. Research has been primarily based on the application of self-report scales, and little has been done to examine the lived experience of participants. The aim of this study was to apply an interpretative phenomenological approach to the experience of participants in a Mindfulness Based Flourishing (MBF) programme, which combines positive psychological interventions with mindfulness in order to more fully understand the impact of their experience on them. Three participants from a completed MBF programme each had a one-off semi-structured interview, the results of which were transcribed verbatim. The resulting texts were analysed, with five themes emerging, which demonstrated the impact of the programme on participants' sense of self and on the nature of their connections with others. While all participants identified benefits accruing from the course, it also presented challenges emotionally as well as in terms of the embedding of knowledge and skills. Future research should look to examine the impact of such programmes in wider cultural and temporal frameworks and should explore the application of grounded theory to identify more theoretical level explanations of the phenomenon.